PENGARUH KEBUTUHAN BERPRESTASI, LOCUS OF CONTROL INTERNAL DAN PENGALAMAN KEWIRAUSAHAAN TERHADAP SIKAP KEWIRAUSAHAAN PADA MAHASISWA - Ma'rifah, Nuvida Nur (Universitas Negeri Surabaya, 2019)
The aims of this study to nalyze the influence of of need for achievement, internal locus of control, and entrepreneurial experiences towards entrepreneurial attitude among students. This research was carried out at the Faculty of economics, State University of Surabaya. The population of this study were 2015 generations of economic education students as many as 328 people with the total sample of 180 people. Data collection are using interviews and questionnaires. The data analysis techniques used are Stuctural Equation Modeling(SEM) analysis with WarpPLS approach. The results of this study indicate that there is a significant influence between the needs of achievement on entrepreneurial attitudes. There is a significant effect between internal locus of control on entrepreneurial attitudes. There is a significant influence between entrepreneurial experience on entrepreneurial attitudes. There is a significant influence between the need for achievement, internal locus of control and entrepreneurial experience on entrepreneurial attitudes.